Application of Religious Moderation Through Tolerance Attitude to Students of PIAUD IAIN Pekalongan Study Program - Miftahul Jannah; Khamim Zarkasih Putro; Ahmad Tabiin (Universitas Cokroaminoto Yogyakarta, 2022)
Moderation of religion in students is very important to discuss, especially in this modern era. Religious moderation can’t be separated from tolerance because it can affect daily life. This study aims to understand how students apply tolerance in religious moderation and to find out how students from the PIAUD IAIN Pekalongan study program foster socialization in religion. The research method used is a qualitative research method. Data collection techniques through the distribution of questionnaires, observations, interviews and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, data display. The results of this study indicate that the students of the PIAUD IAIN Pekalongan study program are able to understand the meaning and concept of religious moderation, the students are able to apply the concept of religious moderation in everyday life through an attitude of tolerance. The cultivation of religious moderation in students must be done so that students are able to have moderate traits and prevent intolerant attitudes towards others and those around them.